Reliable DC voltage generation based on the enhanced performance triboelectric nanogenerator fabricated by nanoimprinting-poling process and an optimized high efficiency integrated circuit. (March 2020) - Yoo, Donghyeon; Lee, Seoulmin; Lee, Jeong-Won; Lee, Kwangseok; Go, Eun Yeong; Hwang, Woonbong; Song, Insang; Cho, Sung Baek; Kim, Do Wan; Choi, Dongwhi; Sim, Jae-Yoon; Kim, Dong Sung
Abstract: Intensive research on triboelectric nanogenerators (TENGs) has been established since they were first introduced, but their application as a practical power source remains to face several challenges. Herein, we report a one-step process of thermal nanoimprinting and simultaneous electric poling to increase the total energy obtained by each cycle of a TENG with a ferroelectric thermoplastic polymer. The synergetic effect generated by the resultant formation of surface topography and the enhancement of effective dipole strength is systematically verified, and a wind energy harvester with enhanced electrical output performance is demonstrated. Furthermore, this paper also presents a novel integrated circuit (IC) that can generate reliable DC voltage even when an intermittent and irregular electrical output of the TENG is supplied. In the automatic control of the moment when the electrical output of the TENG is transferred into the electronic device, the present IC shows a conversion efficiency over 70% even when the input power is about 2.5 μW. This work intensively addresses the issues hindering the utilization of TENGs as a practical and reliable power source and thus may serve as a reference in the development of TENG-based self-powered systems in the future. Graphical abstract: Image 1 Highlights: One-step process of thermal nanoimprinting and electrical poling to enhance the output of a triboelectric nanogenerator. Optimized integrated circuit for triboelectric nanogenerator to generate a reliable DC voltage. Need of electrical poling process to recover dipole strength of ferroelectric polymers after thermal nanoimprinting process.